Pengaruh Keberagaman Gender Dewan Direksi dan Ukuran Dewan Direksi terhadap Kualitas Pelaporan Keuangan di Sektor Kesehatan - Atikah Rahmawati; Rahman Anshari; Muhammad Iqbal Pribadi (Lembaga Pengembangan Kinerja Dosen, 2025)
Purpose. This study aims to determine the influence of gender diversity on the board of directors and the size of the board of directors on the quality of financial reporting in the Health Sector. Methods. This study uses the population of health sector companies listed on the Indonesia Stock Exchange during the period 2014-2023. Through the purposive sampling method, 106 observation data (firm-year) were obtained from companies that published annual reports during the period and compiled financial statements in rupiah. Furthermore, the data were further selected by excluding years in which the company exhibited negative profit management practices, in order to meet the criteria of this study. The data analysis technique used in this study is multiple linear regression analysis supported by hypothesis testing, descriptive statistics and classical assumption tests. Findings. The results of the hypothesis test show that gender diversity in the board of directors has a significant effect on the quality of financial reporting. And the size of the board of directors does not have a significant influence on the quality of financial reporting. Implication. The implications of this study show that gender diversity on the board of directors can be an effective strategy in improving the transparency and quality of financial reporting, especially in the health sector. Therefore, companies are advised to consider gender representation in the preparation of the board of directors structure to strengthen corporate governance.